MITOLOGI TIRTA EMPUL DALAM TEKS USANA BALI: KAJIAN TEOLOGI SOSIAL - I Gede Arya Juni Arta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Hindu theology from the beginning was different from classical theology. Where religion or divinity does not conflict with science. God is not placed in the sky but exists and permeates His creation. Such a conception of God would be difficult to understand in Western theology. In the text of Usana Bali, concrete and solution-based theology or divinity is implied, which is narrated through the mythology of Tirta Empul and the story of Mayadanawa. Where God in his manifestation as Dewa Indra becomes a liberating agent for the social problems of society. Eradicating the evil king Mayadanawa, providing prosperity through abundant water sources, and giving meaning to the Galungan holiday as an effort to improve the quality of life (winning the inner dharma). This research is a literature study, using the Usana Bali text as primary data. The purpose of this research is to explore theological teachings in a mythology, in order to develop the role and social values in it.Keywords: Mythology, Social Theology, Usana Bali